Endovascular repair of severe aortic coarctation, transcatheter aortic valve replacement for severe aortic stenosis, and percutaneous coronary intervention in an elderly patient with long term follow-up - Fallatah, Raneem (J Saudi Heart Assoc, 2018)
To the best of our knowledge, there have not been any reports of total transcatheter approach including stenting of severe coarctation of the aorta (CoA), transcatheter aortic valve replacement (TAVR) for concomitant severe aortic valve stenosis, and percutaneous coronary intervention (PCI) to treat significant coronary artery disease in a single patient. We report a 70-year-old female, who presented with uncontrolled hypertension and acute decompensated heart failure (ADHF) and was found to have severe CoA, severe bicuspid aortic valve (BAV) stenosis, and significant proximal left anterior descending (LAD) coronary artery disease. In a multidisciplinary heart team meeting, we decided to perform an endovascular repair of both cardiac and vascular pathologies using a two-stage approach due to the significant comorbidities; mainly uncontrolled hypertension, type 2 diabetes mellitus, chronic obstructive pulmonary disease, and severe calcifications of the ascending aorta. The procedures were successfully performed and the patient was asymptomatic 30 months later at follow-up and was without any significant gradients across the coarctation or the aortic valve.